(untitled) (Academicia Globe: Inderscience Research, 2022)
The article talks about the foreign policy of the Republic of Uzbekistan in the years of independence on international cooperation.The main emphasis will be on the historical roots of Korean and Uzbek relations, as well as cooperation with the Republic of Uzbekistan in socio-political, economic and cultural spheres during the years of independence.